Predictors of stunting among pediatric children living with HIV/AIDS, Eastern Ethiopia - Dawit Gezahegn; Gudina Egata; Tesfaye Gobena; Berhanu Abebaw (Intelektual Pustaka Media Utama, 2020)
Globally, there were about 3.4 million pediatric children (<15 years of age) who were living with HIV/AIDS. Ethiopia has one of the highest rates of malnutrition in Sub-Saharan Africa. As of 2013, there were about 160,000 pediatric children living with HIV/AIDS in Ethiopia. Even though undernutrition makes it difficult to combat HIV/AIDS, there is paucity of information on the magnitude of stunting and its predictors among seropositive pediatric children in low-income countries like Ethiopia. Institution based quantitative cross sectional study design was employed on 414 randomly selected pediatric (5-15 years) children living with HIV/AIDS in Harari Region and Dire Dawa City Administration Public Hospitals, Eastern Ethiopia. Pretested interviewer administered questionnaire and patient card review was held to collect data. Data were entered through Epi-data and exported to SPSS for analysis. The WHO Anthros plus software was used to calculate the anthropometric indices. Bivariate and Multivariable analysis along with 95%CI were done to identify predictors of stunting. Level of statistical significance was declared at P-value <0.05. The prevalence of stunting was found to be 30.9% (95%CI: 26.0-36.0%). Rural residence [AOR=4.0, (95%CI: 2.22, 7.17)], family monthly income of ≤500 ETB [AOR=5.79, (95%CI: 2.82, 11.60)], being anemic [AOR=3.17, (95% CI: 2.13, 4.93)] and the presence of diarrhea [AOR=6.21, 95% (CI: 3.39, 9.24)] were predictors of stunting. Thus, collaborative measures should be undertaken (to decrease frequent infections and to improve the economic status) to combat chronic malnutrition during HIV/AIDS treatment.